2022
DOI: 10.3389/fcvm.2022.813208
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cardiometabolic Factors in Mediating the Causal Effect of Type 2 Diabetes on Cardiovascular Diseases: A Two-Step, Two-Sample Multivariable Mendelian Randomization Study

Abstract: ObjectiveThe objective of this study is to investigate the roles of cardiometabolic factors (including blood pressure, blood lipids, thyroid function, body mass, and insulin sensitivity) in mediating the causal effect of type 2 diabetes (T2DM) on cardiovascular disease (CVD) outcomes.DesignTwo-step, two-sample multivariable Mendelian randomization (MVMR) study.SettingInternational genome-wide association study (GWAS) consortia data.ExposureType 2 diabetes, blood pressure: systolic blood pressure (SBP), diastol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Compared with conventional observational studies, the possibility of residual confounding and reverse causation is greatly reduced in MR. Being a valuable tool for casual inference, MR has been widely used in the cardiovascular disease field ( 28 , 29 ). We investigated the association of CD with 10 cardiovascular diseases using a two-sample MR design.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional observational studies, the possibility of residual confounding and reverse causation is greatly reduced in MR. Being a valuable tool for casual inference, MR has been widely used in the cardiovascular disease field ( 28 , 29 ). We investigated the association of CD with 10 cardiovascular diseases using a two-sample MR design.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the potential roles of cardiometabolic risk factors in mediating causal effect of T2D on CV disease may help identify treatment targets required to reduce T2D disease progression and CV risk. 3 Several prospective studies, ranging from a duration of 7 months to 19 years, have observed that the proportions of patients with T2D who achieve composite metabolic targets are usually very low, ranging from approximately 5% to 25%, with the higher proportions observed in the United States and the lower proportions in China. [9][10][11] More specifically, a registry study in the United States reported that 10 However, it should be emphasized that only 7.1% of participants were receiving sodiumglucose cotransporter-2 inhibitors or GLP-1RAs.…”
Section: Non-high-density Lipoprotein Cholesterol Target <130 Mg/dl (...mentioning
confidence: 99%
“…The association between diabetes and cardiovascular (CV) health is well known, and the interrelated risk factors of hypertension, elevated fasting glucose, dyslipidaemia, abdominal obesity and elevated triglycerides, collectively known as cardiometabolic disorders, 1 are leading causes of long‐term diabetes complications 2,3 . Adiposity and dysglycaemia are the two main metabolic drivers for cardiometabolic‐based chronic diseases, as applied to the CV endpoints of coronary heart disease, heart failure and atrial fibrillation 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Multiple pleiotropic loci (e.g., CDKN2B-AS1, [5,6] TCF7L2, [6][7][8] HNF1A, [6,7] ALDH2, [5] FTO, [6] CCDC92, [7] APOE, [7] and MASP1 [8] ) are also reported to independently affect both diseases. Mendelian randomization (MR), which uses genetic variants as instrumental variables (IVs) to estimate exposure-outcome causal relationships, has consistently identified a causal association (effect sizes ranging from 1.09 to 1.63) between genetically determined T2DM and CAD [3,7,[9][10][11][12][13][14] (a detailed summarization is shown in Supplementary Figure 1, http://links. lww.com/CM9/B771).…”
Section: Introductionmentioning
confidence: 99%